Penerapan Model Pembelajaran Berbasis Masalah melalui Lesson Study untuk Meningkatkan Hasil Belajar Siswa SMAN 8 Kota Bengkulu - Irwandi Irwandi; Ayu Permata Sari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This study aimed to improve understand the result study by using problem based learning of SMAN 8 Bengkulu. The study applied lesson study activity.  It can be concluded that by using problem-based learning in the form of lesson study activity can improve student’s activity and student’s learning outcomes in SMAN 8 Kota Bengkulu. Based on this research, it can be suggested for the teachers to develop lesson study activity to fix learning quality in order to improve their profesionalisme.Keywords: problem based learning, lesson study, learning result